Glossary Book For Cadets Of Indonesian Railway Academy In English Specific Purpose Program - Widiyanah, Ima; ., Handoko; Damayanti, Ajeng Tyas (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2017)
English specific purpose (ESP) is a learner-centered approach to teaching English as additional language, which focuses on developing communicative competence in specific discipline such as academics, accounting, agrology, business, IT, teaching, and engineering. ESP also defined to meet specific needs of learners. Accordingly, it is important for the cadets to master English for railway in order to prepare them for English technical terminology in working area. This study aimed to identify the problem faced by the cadets of Indonesian Railway Academy and to develop glossary terms based on the cadets’ need. In this study, the writer used research and development (R&D) design. It means that the study designed to develop materials for use in ESP program. The population of this study is the cadets of Indonesian Railway Academy. The number of the subject was 35 cadets from electrical class. The writer used questionnaire and interview to gather the data. The result of the study showed that twenty cadets said that ESP is difficult to learn, they also said that there was different English for general and English for Specific Purpose. Fifteen students said that they enjoyed ESP program and they also said that English is important to learn to get a job. The writer concludes that the cadets of Indonesian Railway Academy Madiun have to develop their knowledge about glossary terms for railway to increase their vocabulary.